2022
DOI: 10.1021/acs.iecr.2c00687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe and La on the Performance of NiMgAl HT-Derived Catalysts in the Methanation of CO2 and Biogas

Abstract: Bulk Ni-based catalysts derived from hydrotalcite-type (HT) compounds show enhanced stability in the hydrogenation of CO2 into CH4, in comparison to their supported counterparts. The composition of the parent hydrotalcite determines the Ni loading and particle size, as well as the basicity of the catalysts. In this work, a comparison between the effect of Fe and La on the performance of NiMgAl HT compounds (Ni/Mg/Al = 25/50/25 atomic ratio) calcined at 600 °C is investigated. After a reduction pretreatment at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…The CO 2 ‐TPD profile of UiO‐66 and NH 2 ‐UiO‐66 (Figure 2f and Table S5, Supporting Information) showed two peaks at ≈110 and ≈220 °C, corresponding to weak Lewis alkaline and medium Lewis alkaline, respectively. [ 19 ] It indicated that the Lewis alkaline sites of NH 2 ‐UiO‐66 were more than that of pristine UiO‐66. It was thus clear that Lewis acidity would increase after UiO‐66 was modified with NO 2 , while the functionalization by NH 2 would improve the amounts of Lewis alkaline.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 ‐TPD profile of UiO‐66 and NH 2 ‐UiO‐66 (Figure 2f and Table S5, Supporting Information) showed two peaks at ≈110 and ≈220 °C, corresponding to weak Lewis alkaline and medium Lewis alkaline, respectively. [ 19 ] It indicated that the Lewis alkaline sites of NH 2 ‐UiO‐66 were more than that of pristine UiO‐66. It was thus clear that Lewis acidity would increase after UiO‐66 was modified with NO 2 , while the functionalization by NH 2 would improve the amounts of Lewis alkaline.…”
Section: Introductionmentioning
confidence: 99%
“…The number of different octahedrally coordinated cations that can be introduced in the brucite-like layers is theoretically unlimited as long as the ionic radius is in the range of 0.65–0.80 Å and 0.62–0.69 Å for the trivalent and divalent cation, respectively, although the most common trivalent Al 3+ is significantly smaller (0.50 Å). However, cations with larger ionic radii and/or higher coordination, such as lanthanides or noble metal cations as well as tetravalent cations (e. g. Zr 4+ , Sn 4+ , and Ti 4+ ), have been introduced in M 2+ M n+ -LDHs or in multicationic LDHs containing a large number of divalent and/or trivalent cations [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Focusing now on CO 2 transformation using green hydrogen, Tsubaki et al reported the direct conversion of CO 2 to aromatics using a bifunctional zeolite-based catalyst, Herskovitz et al. investigated the process configuration and technoeconomic aspect of CO 2 hydrogenation to renewable liquid fuels, Fan et al reported the conversion of CO 2 to light olefins using metal oxides, Pieta et al discussed the conversion of CO 2 to CO and methane using non-noble-metal-supported catalysts, Wang et al reported the conversion of CO 2 to methanol using a modified Cu/ZnO/Al 2 O 3 catalyst, Ma et al provided a short review on the formation of methanol from CO 2 by direct and indirect hydrogenation pathways, Gonzalez-Velasco et al investigated kinetics, model discrimination, and parameters of CO 2 methanation, Ding et al and Benito et al studied the mechanism of CO 2 methanation and promoter effect on the catalyst performance. For the transformation of CO 2 using chemicals other than green hydrogen, Ateka et al reported the joint conversion of CO 2 with syngas to synthesize light olefins, Liang et al and Sun et al prepared nickel-based catalysts for CO 2 reforming of methane, Jin et al investigated carbon fixation via the gasification of polypropylene and polycarbonate in a CO 2 environment, Song et al revealed mechanistic insights into the promotional effect of CO 2 on propane aromatization, and Liu et al reported enhanced CO 2 decomposition via frosted dielectric barrier discharge plasma .…”
mentioning
confidence: 99%